The use of an enterprise ontology to support knowledge management in software development environments - Villela,Karina (2005)
Software engineering is knowledge-intensive activity and knowledge is thought to be the most important asset in an organization. Therefore this paper presents an approach to support Knowledge Management in Software Development Environments that is strongly based on ontologies: Enterprise Oriented Software Development Environments. After describing the components of such environments, this paper focuses on the Enterprise Ontology and on three tools developed based on this ontology: a 'yellow pages' tool which shows the distribution of competencies in the organization, a tool to support the allocation of people to software projects and a graphic tool for representing and visualizing organizational processes.